Lived Experiences of Women after Emergency Peripartum Hysterectomy: A Qualitative study in Peshawar, Pakistan. - Nusrat Begum, Najma Naz, Dildar Muhammad, Sabiha Khanum, Tariq Rahim, Sheraz Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emergency Peripartum Hysterectomy (EPH) is a type of hysterectomy which is performed in emergency and life-threatening situations like postpartum hemorrhage. Aim: To explore the lived experiences of women after EPH. Methods: A qualitative phenomenological study was conducted in Lady Reading Hospital (LRH) Peshawar, Khyber Pakhtunkhwa (KP) to explore the lived experiences of women after EPH. A total of 10 participants were included in the study. Data were collected using interview guide, audio and written data were recorded. Thematic analysis was done using thematic analysis techniques. Results: Overall, ten participants were included in the study. 117 codes were generated from the data which helps in creating five themes about the experiences of women after EPH. The women experience profound grief, needs for support, needs for information, bonding and fear. Conclusion: The findings of the study concluded that women after EPH experience profound grief, need of support, need of information, bonding, and fear. Keywords: Women, Emergency peripartum hysterectomy, lived experiences, Qualitative Study